Upaya Peningkatan Pronunciation Siswa Melalui Metode Song - Khudriyah Khudriyah (An Naf'ah: Jurnal Pengabdian Masyarakat, 2024)
Pronunciation is a science that studies techniques/procedures for pronouncing English vocabulary. This technique should not be ignored when learning English because errors in pronunciation can cause misunderstandings of meaning. This this study aimed to improve the pronunciation skills of MTs al Urwatul Wutsqo Bulurejo Jombang students by using the singing method. Based on the results, it can be concluded that the mentoring of English vocabulary pronunciation was very effective and had a positive impact, where students' English vocabulary pronunciation abilities increased significantly, because based on the paired sample test there was a significant comparison between the mean before and after the mentoring where the mean was found. (41.00, increased to 60.00) and the results of t count > t table (9, 628 > 2, 0902) so it can be concluded that this mentoring was successful.